Urgensi Penerapan Celestial Management Bagi Sumber Daya Manusia Di Bank Syariah - Trimulato Trimulato (Muslim Heritage, 2016)
Abstract: Islamic banking currently has a strong legal law with the presence of the law number 21 of 2008 on banking syari'ah.Hal This adversely affects the existence of the banking Shari'ah are increasingly in demand by many. Islamic bank continues to grow and continue to open office services in various areas. Thus iru development of Islamic banks must be matched with adequate resources and qualified. Noted labor in Islamic banks continued to grow, from November 2014 to November 2015 grew to 23.51%. Not only the quantity but the quality should also be considered, it takes a celestial concept should be applied for the Management of human resources in Islamic banks. This paper uses a descriptive qualitative limitations in this paper is focused on the human resources that exist in the Islamic bank. The need for the application of celestial management for human resources in the bank syariahi. The results of this paper that the human resources in Islamic banks is growing, then the need for the application of celestial management for human resources in Islamic banks to create good quality. Because the Islamic bank is an institution whose business is inseparable from the rule of religion or spiritual aspect.Abstrak: Perbankan syari’ah saat ini telah memiliki payung hukum yang kuat dengan hadirnya undang-undang nomor 21 tahun 2008 tentang perbankan syari’ah.Hal ini sangat berpengaruh terhadap eksistensi dari perbankan syari’ah yang semakin diminati oleh banyak kalangan. Bank syari’ah terus berkembang dan terus membuka layanan kantor di berbagai daerah. Maka dari iru perkembangan bank syariah harus diimbangi dengan sumber daya yang mencukupi dan berkualitas. Tercatat tenaga kerja di bank syariah terus bertambah, dari November 2014 sampai November 2015 mengalami pertumbuhan hingga 23,51%. Tidak hanya dari kuantitas tapi kualitas juga harus diperhatikan, dibutuhkan sebuah konsep celestial manajement yang harus diterapkan bagi sumber daya manusia di bank syariah. Penulisan ini menggunakan jenis deskriptif kualitatif, Batasan dalam tulisan ini difokuskan pada sumber daya manusia yang ada di bank syari’ah. Perlunya penerapan celestial management bagi sumber daya manusia di bank syariahi. Hasil dari tulisan ini bahwa sumber daya manusia di bank syariah mengalami pertumbuhan,kemudian perlunya penerapan celestial management bagi sumber daya manusia di bank syariah untuk menciptakan kualitas yang baik. Karena bank syariah adalah lembaga bisnis yang tidak terlepas dari aturan agama atau aspek spiritual.